Forest restoration and biodiversity enhancement across China: Regional case insights into ecosystem function recovery and conservation outcomes - Peng Zhang; Lixiao Ni; Hind Alofaysan; Mammadova Simuzar Sultan; Norboy Karimov (Ecological Indicators)
Freshwater ecosystems are increasingly subjected to multiple anthropogenic stressors, notably pesticide contamination and nutrient enrichment, which jointly threaten biodiversity and impair key ecosystem functions. This study conducts a comprehensive ecological risk assessment to evaluate the interactive effects of these stressors on freshwater biodiversity and ecological processes across diverse aquatic systems in China. Focusing on streams, rivers, and lentic environments in agriculturally intensive regions such as the Yangtze River Basin, the North China Plain, and parts of Yunnan Province, we integrate water quality analyses, biotic surveys, and experimental mesocosm data collected between 1995-2023. Taxonomic groups assessed include aquatic macroinvertebrates, fish, periphyton, and microbial communities. Our findings reveal that while moderate nutrient inputs initially stimulate primary production, combined exposure to high nutrient loads and pesticide mixtures leads to trophic imbalances, reduced species richness, and altered food web structures. Synergistic interactions between herbicides and excess nitrogen/phosphorus were particularly detrimental to invertebrate diversity and periphyton biomass, with significant downstream effects on ecosystem respiration and nutrient cycling. Multivariate risk models indicate that phosphorus availability and pesticide persistence are key predictors of biodiversity loss and functional degradation. Temporal analysis suggests that ecosystems with long-term exposure (>10 years) display reduced resilience and slower recovery even after pollutant reduction. Additionally, biodiversity impacts varied by region, with upland streams showing greater sensitivity compared to lowland rivers. This study underscores the urgent need for integrated watershed management approaches that limit agrochemical inputs, monitor ecological indicators, and prioritize restoration in biodiversity hotspots. Policymakers should enforce region-specific water quality thresholds, promote sustainable agriculture, and fund longitudinal studies to track ecological recovery and prevent irreversible ecosystem shifts.